Exposure to antazoline‐naphazoline eye drops during pregnancy and the risk of congenital malformations: a Danish nationwide cohort study. Issue 5 (26th November 2018) - Thomseth, Vilde; Cejvanovic, Vanja; Jimenez‐Solem, Espen; Poulsen, Henrik E.; Utheim, Tor Paaske; Andersen, Jon T.
Abstract: Purpose: To investigate whether exposure to antazoline‐naphazoline eye drops in the first trimester of pregnancy was associated with an increased risk of malformations in humans. Methods: All women giving live birth between 1997 and 2011 in Denmark were included in this nationwide cohort study. All women redeeming at least one prescription of antazoline‐naphazoline eye drops during the first 84 days of pregnancy were identified. Logistic regression was used to estimate the odds ratios of malformations among exposed offspring compared to non‐exposed offspring. Results: We identified 977 706 births between 1997 and 2011. A total of 3061 women (0.32%) were exposed to antazoline‐naphazoline eye drops in the first trimester of pregnancy. The rate of congenital malformations was 3.0% ( n  = 93) in exposed offspring and 3.5% ( n  = 33 594) in unexposed offspring. First‐trimester exposure to antazoline‐naphazoline was not associated with major congenital malformations overall (odds ratio: 0.88, 95% confidence interval: 0.71–1.09) or with any specific major malformation. The number of redeemed prescriptions was unchanged during all trimesters of pregnancy as compared to before and after pregnancy (p < 0.05). Conclusion: Exposure to antazoline‐naphazoline eye drops in the first trimester of pregnancy appears not to be associated with increased teratogenic risk.